THE EFFECT OF ANTI FRAUD STRATEGY ON FRAUD PREVENTION IN BANKING INDUSTRY - Nurul Alfian; Tarjo Tarjo; Bambang Haryadi (Association of Certified Fraud Examiners Indonesia Chapter, 2017)
ABSTRACTThe purpose of this study is to examine the effect of anti fraud strategy on fraud preventionin in banking industry. The data are collected through questionnaires distributed to front liners, marketing, and back office. The sampling technique used is proportionale sampling method with 80 respondents. The research data are analysed using quantitative method, particularly explanatory research approach. In this regard, the researchers use Structural Equation Model (SEM) and Partial Least Square (PLS) with Warrpls 5.0 program. The findings of this study show that prevention pillar, detection pillar and investigation pillar have an effect on fraud prevention in banking industry.